Hermeneutics as a Metatheoretical Framework for Library and Information Science - Vamanu, Iulian (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper discusses the relevance of hermeneutical interpretivism for Library and Information Science research. It surveys the literature that relies on a hermeneutical framework, points to divisions and gaps in this literature, and outlines a systematic and integrative hermeneutical framework that addresses these problems and opens up new venues for future Library and Information Science research. Cet article discute de la pertinence de l’interprétativisme herméneutique pour la recherche en bibliothéconomie et en sciences de l'information. Il passe en revue la littérature qui s'appuie sur un cadre herméneutique, indique des divisions et des lacunes dans cette littérature et définit un cadre herméneutique systématique et intégratif apte à traiter ces problèmes et à ouvrir de nouvelles possibilités pour la recherche future en bibliothéconomie et en sciences de l'information.